2020
DOI: 10.1186/s10086-020-01909-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-polarization dynamics and conformational study of variously sized cellulose crystallites using solid-state 13C NMR

Abstract: Cellulose forms crystalline fibrils, via biosynthesis, that can be just a few nanometers wide. The crystallinity is a structural factor related to material performance. Recently, many routes to isolate these fibrils as nanocellulose have been developed, and there exist various types of nanocellulose with different crystallinities. Quantitative assessment of the crystallinity of nanocellulose is thus essential to advance knowledge in the high performance and functionality of such materials. Solid-state 13C cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…CP/MAS 13 C NMR spectroscopy. CP/MAS 13 C NMR measurements were performed using a JEOL JNM-ECAII 500 spectrometer (JEOL Ltd., Tokyo, Japan) equipped with a 3.2-mm HXMAS probe and ZrO2 rotors at 125.77 MHz for 13 C. The samples were spun at 15000 Hz and the 90° proton decoupler pulse width, contact time, and relaxation delay were set to 2.5 μs, 2 ms, and 5 s, respectively 32 . Adamantane was used as the internal standard for the 13 C chemical shifts.…”
Section: Methodsmentioning
confidence: 99%
“…CP/MAS 13 C NMR spectroscopy. CP/MAS 13 C NMR measurements were performed using a JEOL JNM-ECAII 500 spectrometer (JEOL Ltd., Tokyo, Japan) equipped with a 3.2-mm HXMAS probe and ZrO2 rotors at 125.77 MHz for 13 C. The samples were spun at 15000 Hz and the 90° proton decoupler pulse width, contact time, and relaxation delay were set to 2.5 μs, 2 ms, and 5 s, respectively 32 . Adamantane was used as the internal standard for the 13 C chemical shifts.…”
Section: Methodsmentioning
confidence: 99%
“…The density and porosity of nanocellulose can be measured using a helium pycnometer. Daicho et al (2020) reported the density of pure native celluloses, such cotton and tunicin, are approximately 1.60 g/cm 3 using helium pycnometer. In order to study the elemental composition on nanocellulose surface, X-ray photoelectron spectroscopy (XPS) technique could be used (Jordan et al, 2019).…”
Section: Properties and Characterization Of Nanocellulosementioning
confidence: 99%
“…In the NMR spectra, the C4 and C6 carbon atoms are distinguishable into crystalline and noncrystalline signals. The signal ratio of C4 crystalline and noncrystalline phases can be used for calculation of crystallinity index (CI) value of nanocellulose (Daicho et al, 2020). However, nanocellulose tends to agglomerate while drying, therefore solid-state characterization may reflect certain structural changes from drying and not necessarily the precise nature of the individual nanocellulose (Jiang et al, 2014).…”
Section: Properties and Characterization Of Nanocellulosementioning
confidence: 99%
“…CP/MAS 13 C NMR measurements were performed using a JEOL JNM-ECAII 500 spectrometer (JEOL Ltd., Tokyo, Japan) equipped with a 3.2-mm HXMAS probe and ZrO2 rotors at 125.77 MHz for 13 C. The samples were spun at 15000 Hz and the 90° proton decoupler pulse width, contact time, and relaxation delay were set to 2.5 μs, 2 ms, and 5 s, respectively. 31 Adamantane was used as the internal standard for the 13 C chemical shifts.…”
Section: = 180°− 180°mentioning
confidence: 99%